Sustainable value chain financing for smallholder agricultural production in the Philippines (2022)
Cognizant of the value, contribution, and challenges in the country’s
agricultural finance, the government has intensified its lending programs to
help the sector, particularly smallholders, thus, boosting affordable and easy
access retail lending in recent years. Despite these efforts, however, significant
problems remain, including the lack of markets and low prices, which have had
significant implications on the overall repayment capacity and credit rating of
small farmers and fisherfolk in the Philippines. Indeed, lending programs are
unlikely to become successful if financing and production are not viewed in
the bigger context of value chain financing. This paper looks into the farmers
and fisherfolk’s financing ecosystem and provides recommendations on how the
existing value chain financing in the Philippines can become more inclusive and
sustainable for them.
Keywords: Agricultural productivity